DISKURSUS SURAT AL-FATIHAH (Telaah Dalam Perspektif Maqashid) - lathifah munawaroh (Islam Futura, 2018)
This paper is the exposition of tafsir in the frame of maqashid al-Shariah. Generally the discussion of maqashid al-shariah is about the purpose of sharia law, either general purpose or special purpose on the laws that God has set. But then the discussion maqashid al-Shariah shifted on the study of the Qur'an called maqashid al-Qur'an. If the Maqashid al-Shari'ah is more focused on the purpose of establishing Islamic law, while the verses of the Qur'an do not all contain Islamic laws. However, it is precisely on the scope of maqashid al-qur'an beyond the legal issues that are only a small part of the Qur'an. From here the scholars' come with the study of maqashid al-Qur'an pioneered by Abu Hamid al-Ghazli through his book, Jawahir al-Qur'an, and forwarded by Islamic thinkers such as Abduh, Rashid Rida, Badiuzzaman Said Nursi, Ibn Asyur , Muhammad Al-Ghazali, Izzat Darwazah, and so forth. The main points of the Qur'an are called maqashid al-Qur'an. The focus of maqashid al-Qur'an in this paper is surah al-Fatihah which is called Ummul Kitab or Ummul Quran. This surah is the key of a Muslim prayer of 17 rakaat for 5 times a day overnight. If one understands the maqashid al-quran on this surah, then this will make him understand the purposes of God in this surah.